2022
DOI: 10.1002/ajhb.23856
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in growth status: A cross‐sectional survey among Tibetan adolescents living at three different high altitudes in Tibet, China

Abstract: To explore the regional and age variation in growth status and ageby-site interaction effect on the growth status among Chinese Tibetan adolescents at different altitudes in Tibet, China. Methods:The research was conducted in three regions of Tibet, China:Nyingchi (average altitude 3100 m), Lhasa (average altitude 3650 m), and Nagqu (average altitude 4500 m). A total of 3817 Chinese Tibetan adolescents aged 12-18 years were tested for height, weight, chest circumference, and waist circumference. One-way ANOVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Some of the scholars' studies emphasize the mechanisms of the natural and built environment that influence adolescents' physical fitness. For example, the altitude of the area where they are located is the main natural environmental factor influencing the development of physical fitness and form in children and adolescents [44][45][46]. Existing studies have shown that there is a highly significant correlation between human aerobic capacity and altitude, and that appropriate altitude can effectively enhance human aerobic capacity [47].…”
Section: Factors Influencing Physical Fitnessmentioning
confidence: 99%
“…Some of the scholars' studies emphasize the mechanisms of the natural and built environment that influence adolescents' physical fitness. For example, the altitude of the area where they are located is the main natural environmental factor influencing the development of physical fitness and form in children and adolescents [44][45][46]. Existing studies have shown that there is a highly significant correlation between human aerobic capacity and altitude, and that appropriate altitude can effectively enhance human aerobic capacity [47].…”
Section: Factors Influencing Physical Fitnessmentioning
confidence: 99%
“…Participants living at sea level tend to be taller, heavier, and have a higher body mass index (BMI), and waist circumference (WC) relative to those living at HA ( 9 ). Previous studies have shown that the growth indicators, such as height, weight, chest circumference, and WC, differ among Chinese Tibetan adolescents at different altitudes ( 10 ). However, there is a lack of systematic research on the differences in human body composition among Tibetan college students at different altitudes.…”
Section: Introductionmentioning
confidence: 99%